Penguatan Daya Ingat Santri Melalui Bimbingan Kelompok Metode Tanya Jawab di TPQ Baiturrahman - Hayatul Mala; Achmad Zainur Roziqin (Asosiasi Riset Ilmu Tanaman Dan Hewan Indonesia, 2025)
This community service activity was carried out with the aim of improving the memory of students at the Baiturrahman Islamic Boarding School (TPQ) through the implementation of group guidance based on an interactive question and answer method. The background of this program is based on the problem of low retention of religious material that has been learned by students, so the learning approach is needed that does not only emphasize memorization, but also activates the process of critical and in-depth thinking. In its implementation, the activity is designed to involve students directly in group discussions guided by a facilitator. The questions posed are structured in such a way as to stimulate repetition of information, encourage logical reasoning, and help students connect the learning material with real experiences in everyday life. Through this process, students are not only asked to answer questions but are also trained to develop broader answers, thereby strengthening understanding and improving communication skills. This program also prioritizes a fun, collaborative, and participatory learning atmosphere so that students feel more motivated to actively participate. Evaluation results show a significant increase in students' ability to remember, understand, and re-present learning material more quickly, accurately, and coherently. Furthermore, this activity also has a positive impact on increasing students' self-confidence in the learning process and strengthening collaborative skills among group members. Thus, group guidance using the question-and-answer method can be considered an effective learning strategy for strengthening students' memory and increasing their learning motivation.